Relevancy of the "Health Belief Model” on Behavior in Seeking Treatment among Families of Patients with Mental Disorders in the Work Area of the Public Health Center Taman Sidoarjo East Java - Eka Sari, Jayanti Dian; Riris Diana Rachmayanti; Namirah Aulia Rizki Herdianisah; Andrei Ramani; Rachmah Indawati; Aninditya Ardhana Riswari; Ismayani; Anysiah Ely Yulianti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Mental health is a part that is related to health and wellness. One of the indicators in Gerakan Masyarakat (GERMAS) [”society movement”] stated that people with mental disorders should be treated and not abandoned. Nevertheless, nowadays it is still common to find people with mental disorders that do not receive proper medical care. Aims: The aim of this research is to measure cues to action and self-efficacy of the family behavior in seeking treatment for people with mental disorders within the work area of the Public Health Centre Taman Sidoarjo. Method: This research utilized the observational method with the cross-sectional study design and was analyzed with the Health Belief Model (HBM) theory approach. Result: The statistical analysis results using the Pearson Chi-Square test with a significance level of < 0.05 showed a p-value of 0.034 for perceived susceptibility and severity, a p-value of 0.180 for perceived threat, a p-value of 0.009 for perceived benefit, a p-value of 0.696 for perceived barriers, a p-value of 0.555 for self-efficacy, and p-value of 0.099 for cues to action. Based on these results, it can be concluded that perceived susceptibility and severity have a positive relationship with the family behavior in seeking treatment, which means the more perceived susceptibility, and severity increase, the more the family behavior in seeking treatment for people with mental disorders increases. Conclusion: Likewise, perceived benefit has a positive relationship with the family's behavior in seeking treatment. However, perceived threat, perceived barriers, self-efficacy, and cues to action have no relationship with the family behavior in seeking treatment for people with mental disorders.